Do health checks improve risk factor detection in primary care? Matched cohort study using electronic health records - Forster, Alice S. (J Public Health (Oxf), 2016)
BACKGROUND: To evaluate the effect of NHS Health Checks on cardiovascular risk factor detection and inequalities. METHODS: Matched cohort study in the Clinical Practice Research Datalink, including participants who received a health check in England between 1 April 2010 and 31 March 2013, together with matched control participants, with linked deprivation scores. RESULTS: There were 91 618 eligible participants who received a health check, of whom 75 123 (82%) were matched with 182 245 controls. After the health check, 90% of men and 92% of women had complete data for blood pressure, total cholesterol, smoking and body mass index; a net 51% increase (P < 0.001) over controls. After the check, gender and deprivation inequalities in recording of all risk factors were lower than for controls. Net increase in risk factor detection was greater for hypercholesterolaemia (men +33%; women +32%) than for obesity (men +8%; women +4%) and hypertension in men only (+5%) (all P < 0.001). Detection of smoking was 5% lower in health check participants than controls (P < 0.001). Over 4 years, statins were prescribed to 11% of health -check participants and 7.6% controls (hazard ratio 1.58, 95% confidence interval 1.53–1.63, P < 0.001). CONCLUSION: NHS Health Checks are associated with increased detection of hypercholesterolaemia, and to a lesser extent obesity and hypertension, but smokers may be under-represented.